Hepatitis E in transfusion‐dependent thalassaemia patients, in Greece: a single centre experience. Issue 7 (10th September 2017) - Klonizakis, P.; Gioula, G.; Exindari, M.; Apostolou, C.; Kotsiafti, A.; Vlachaki, E.
Abstract : Hepatitis E is considered an emerging disease that may be a threat in both developing and industrialized countries all over the world. The risk of chronic hepatitis E virus infection is higher among immunocompromised patients. This study aimed to assess the status of hepatitis E infection in patients with transfusion‐dependent thalassaemia from a single centre, in Greece. Our results suggest that the prevalence of hepatitis E infection in this group of patients is low.